A Review of Cybersecurity and Biometric Authentication in Cloud Network - Reddy, Manjunath; Chisty, Nur Mohammad Ali; Bodepudi, Anusha (Engineering International, 2022)
Cloud computing uses few resources to give customers complete distant services via the internet. Data privacy, security, and reliability are major issues with cloud computing. Security is the biggest issue. This study discusses the biometrics framework and safe cloud computing identity management method. This paper discusses cloud computing security challenges and reviews cloud access framework approaches. It describes a novel fingerprint access-based authentication system to protect cloud services from DOS and DDoS attacks. This biometrics-based system can secure cloud services from illegal access. This study addresses cloud security and privacy via biometric face recognition. Cloud users' security and privacy are protected via biometrics recognition. This article discusses CPS and its applications, technologies, and standards. SIGNIFICANT DIFFICULTIES AND CHALLENGES ARE FOUND IN reviewing CPS security weaknesses, threats, and attacks. Presenting and analyzing current security measures and their key drawbacks. Finally, this extensive examination yields various recommendations.
Keywords: Cloud Network; Cyber Security; Privacy Preservation; Biometrics Identification; Encrypted Biometrics